Folktales as an educational tool: Building character and enhancing communication skills in children - Srihati, Dewanti; Rini, Endah Febri Setiya; Salshabella, Dhea Clara; Siswanto, Predy; Afriani, Febi; Aryaguna, Aland; Putri, Rahma Dhian Karisma; Intan, Yosefina Safira; Solihat, Iis; Lera, Kristoforus (Research Journal in Advanced Humanities, 2025)
Children's literature, particularly folktales, serves as an effective tool for fostering character development and enhancing communication skills in children. This study explored the use of folktales as a means of improving the character and communication skills of students in Kedurang. The researchers employed observation, interviews, and document analyses to gather the necessary data. The findings indicate that folktales were commonly used by the community in Kedurang to promote values such as helping others, compassion, friendship, and courage in facing challenges. Furthermore, through storytelling activities, folktales were utilized to train children in communication skills. The stories shared were diverse, including tales like "Beteri and the Deer" ("Beteri dan Rusa"), "Sinamnam," "The Buffalo and the Mousedeer" ("Si Kerbau dan Si Kancil"), and "The Tortoise and the Eagle" ("Si Kura-Kura dan Si Elang"). These stories reflect the local wisdom of the Kedurang community. The people of Kedurang also believe that folktales are an effective way to train children to be good listeners and speakers. This study has implications for the preservation of children's literature, the enhancement of communication skills through storytelling, and the implementation of character education through children's literature.